2020
DOI: 10.4314/aas.v17i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Utility of World Society of Emergency Surgery Sepsis Severity Score in Predicting Outcomes of Intra-abdominal Infections

Abstract: Background: Intra-abdominal infections are classified as simple or complicated. Many tools have been studied to predict risk factors and outcomes of patients with intra-abdominal infections. None of these tools has been adopted for patient care at the Kenyatta National Hospital (KNH), Kenya. Objective: To determine the utility of the World Society of Emergency Surgery (WSES) Sepsis Severity Score in predicting short-term outcomes of patients managed for complicated intra-abdominal infections.�… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many studies confirmed the accuracy of the WSES SSS in predicting mortality in patients with peritonitis [16,17,18].…”
Section: Introductionmentioning
confidence: 84%
“…Many studies confirmed the accuracy of the WSES SSS in predicting mortality in patients with peritonitis [16,17,18].…”
Section: Introductionmentioning
confidence: 84%